Enhanced 1.5 μm emission of Er3+-doped multifunctional Bi2ZnOB2O6 microcrystals. Issue 18 (16th April 2019) - Jaroszewski, Konrad; Zhezhera, Taras; Gluchowski, Pawel; Marciniak, Lukasz; Chrunik, Maciej; Majchrowski, Andrzej; Kasprowicz, Dobroslawa
Abstract : The efficiency of the 1.5 μm emission associated with the 4 I13/2 → 4 I15/2 transition of Er 3+ ions of a series of Er 3+ and Yb 3+ /Er 3+ -doped Bi2 ZnOB2 O6 microcrystalline powders was investigated. Abstract : The efficiency of the 1.5 μm emission associated with the 4 I13/2 → 4 I15/2 transition of Er 3+ ions of a series of Er 3+ and Yb 3+ /Er 3+ -doped Bi2 ZnOB2 O6 microcrystalline powders was investigated. Bi2 ZnOB2 O6 is an excellent nonlinear optical material as well as a good host matrix for luminescent rare-earth ions. The investigated powders were synthesized by means of the modified Pechini method and their orthorhombic structure with Pba 2 space group were confirmed by XRD measurements. The vibrational properties of Bi2 ZnOB2 O6 :Yb 3+ /Er 3+ were studied using μ-Raman spectroscopy. The low phonon energy of the Bi2 ZnOB2 O6 matrix allows effective phonon assisted energy transfer between rare-earth ions and/or multiphonon relaxation processes of rare-earth ions. It was revealed that the intensity of the 1.5 μm emission under 980 nm excitation increased with increasing Er 3+ concentration (from 0.5 to 3.0 at%) for Bi2 ZnOB2 O6 :Er 3+, while for co-doped Bi2 ZnOB2 O6 :Yb 3+ /Er 3+ systems a significant increase in this emission was observed for the optimal Yb 3+ /Er 3+ concentration (1.5/0.5 at%). Moreover, the intensity of the 1.5 μm emission decreases with increasing temperature for all investigated samples. Additionally, Bi2 ZnOB2 O6 :Yb 3+ /Er 3+ powders exhibit effective up-conversion luminescence in the visible range under 980 nm excitation. In the up-conversion spectra of Bi2 ZnOB2 O6 :Yb 3+ /Er 3+ powders, the bands corresponding to green and red emission of Er 3+ ions ( 2 H11/2 → 4 I15/2 / 4 S3/2 → 4 I15/2 and 4 F9/2 → 4 I15/2 transitions, respectively), as well as the bands at about 487 nm (blue emission) associated with second harmonic generation produced by the Bi2 ZnOB2 O6 matrix were detected. The results indicate a potential for application of Bi2 ZnOB2 O6 :Yb 3+ /Er 3+ powders as effective multifunctional new-generation photonic materials.